2013
DOI: 10.1186/1472-6963-13-148
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year results of quality assurance in radiotherapy chart round

Abstract: BackgroundThe Royal Australian and New Zealand College of Radiologists (RANZCR) initiated a unique instrument to audit the quality of patient notes and radiotherapy prescriptions. We present our experience collected over ten years from the use of the RANZCR audit instrument.MethodsIn this study, the results of data collected prospectively from January 1999 to June 2009 through the audit instrument were assessed. Radiotherapy chart rounds were held weekly in the uro-oncology tumour stream and real time feedback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Patient comorbidities or compliance will sometimes necessitate deviation from accepted guidelines . Resources and clerical issues can also impact on documentation and numbers of patients discussed at multidisciplinary meetings . It is also important to note that non‐adherence to guidelines does not necessarily mean that the patient received suboptimal care, as long as the plan can be justified and has been peer‐reviewed .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient comorbidities or compliance will sometimes necessitate deviation from accepted guidelines . Resources and clerical issues can also impact on documentation and numbers of patients discussed at multidisciplinary meetings . It is also important to note that non‐adherence to guidelines does not necessarily mean that the patient received suboptimal care, as long as the plan can be justified and has been peer‐reviewed .…”
Section: Discussionmentioning
confidence: 99%
“…This was a retrospective audit, and it is well known that clinical audits are best completed prior to the patient starting treatment so that any potential errors can be picked up . Any future studies using this audit tool should be conducted prospectively and include an assessment of how often the audit triggered a change to management and if it had an effect on treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Several authors have described the potential of peer review to indirectly improve quality of care in radiotherapy, both at the general practice level 1;10 or within specific institutions. [11][12][13][14][15][16] In addition, surveys of Canadian ROPs have provided quantitative evidence regarding the perceived benefits of peer review. 7;8 A recent pan-Canadian survey showed that ROPs rated the indirect benefits of peer review as highly important, including the impact of peer review on reducing variation in practice, improving treatment policies, and contributing to continuing professional education.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Like paper records, EHR systems may suffer from data inaccuracy or even erroneous data. A study of radiotherapy service suggests that real-time audit with feedback is an effective tool in assessing the standards of documentation [39]. More generally, based on a comprehensive expert survey, it has been argued that EHR systems should be certified in order to ensure their quality [40], though the evidence for the utility of this proposal is not very clear.…”
Section: Data Quality Of the Ehr Systemmentioning
confidence: 99%